CO2 binding capacity of alkali-activated fly ash and slag pastes - Nedeljković, Marija; Ghiassi, Bahman; Melzer, Stefan; Kooij, Chris; Laan, Siege van der; Ye, Guang (Elsevier, 2018)
Quantification of the CO2 binding capacity of reinforced concrete is of high importance for predicting the carbonation potential and service life of these structures. Such information is still not available for alkali activated materials that have received extensive attention as a sustainable substitute for ordinary Portland cement (OPC)-based concrete. To address this gap, this paper evaluates the CO2 binding capacity of ground powders of alkali activated fly ash (FA) and ground granulated blast furnace slag (GBFS) pastes under accelerated carbonation conditions (1% v/v CO2, 60% RH, 20 °C) for up to 180 days. The CO2 binding capacity, the gel phase changes, and the carbonate phases are investigated with complementary TG-DTG-MS, FT-IR and QXRD techniques.